Association of glycosylated hemoglobin with mortality of patients in intensive care unit: a prospective observation study. - Damera Seshi Kumar; Seema Balkrishna Wasnik; Amlendu Yadav; Rupesh Yadav (Critical Care Innovations, 2024)
INTRODUCTION: Glycated hemoglobin (HbA1c) is the most commonly used clinical test to estimate mean blood glucose during the past 2 to 3 months. In addition to diagnostic purposes, the HbA1c level also predicts diabetes complications. The aim of this study was to determine the association of glycosylated hemoglobin with mortality in intensive care unit (ICU). MATERIALS AND METHODS: A prospective observational study was conducted in the ICU with a total of 281 patients. These patients were classified into two groups based on their HbA1c levels: one group with HbA1c level < 6.5 % and another group with HbA1c level ≥ 6.5%. The following data were collected during the study period. Clinical details and scores such as the APACHE II score (Acute Physiology and Chronic Health Assessment) and daily SOFA (Sequential Organ Failure Assessment) scores for the period of stay in the ICU. ICU morbidities as the need for mechanical ventilation, the use of inotropes / vasopressors, the length of stay in the ICU, and the requirement of renal replacement therapy (RRT). The outcome measures were ICU mortality and 28-day mortality. RESULTS: Of 281 patients admitted to the ICU for more than 48 hours, 157 patients (55.9%) had HbA1c levels < 6.5%, with the remaining 124 (44.1%) had levels ≥ 6.5%. ICU mortality was present in 107 (38.07%) cases. ICU mortality was higher in patients in the HbA1c ≥ 6.5% group compared to the HbA1c < 6.5% group. This was statistically significant (p-value <0.001). Mortality at 28 days was observed in 125 (44.48%) cases. Patients with an HbA1c value ≥ 6.5%, there was a higher mortality at 28 days compared to patients with an HbA1c value < 6.5%. This was found to be statistically significant (p-value <0.001). CONCLUSIONS: The study showed that glycated hemoglobin levels (HbA1c) levels ≥ 6.5% had a significantly higher mortality rate compared to the patient in the HbA1c level < 6.5%.